The Prison Media Complex: Labour, Technology and Communication Infrastructures in the Prison System - Fredrik Stiernstedt; Anne Kaun (tripleC: Communication, Capitalism & Critique)
Prisons are a recurring topic and backdrop in the popular culture of the Global North. They often serve as spectacular environments that seem far removed from most people’s everyday lives. This article develops the notion of the prison media complex and discusses material entanglements between prisons and private media industries via the production of media technologies, consumption of communication, and technology development in the prison sector. The article seeks to answer the question of how we can conceptualise the prison media complex (PMC) from a materialist perspective. Taking the Swedish context as a starting point, we analyse the economic and material connections that characterise the PMC in this national context. Drawing on archival data, participant observations at prison technology tradeshows and a prison sector conference, as well as freedom of information requests, we bring nuance to the picture of media and communication technologies, as technologies of freedom are also based on unfreedom and captivity.